2019
DOI: 10.3390/w11091938
|View full text |Cite
|
Sign up to set email alerts
|

Flood Monitoring in Vegetated Areas Using Multitemporal Sentinel-1 Data: Impact of Time Series Features

Abstract: Synthetic Aperture Radar (SAR) is particularly suitable for large-scale mapping of inundations, as this tool allows data acquisition regardless of illumination and weather conditions. Precise information about the flood extent is an essential foundation for local relief workers, decision-makers from crisis management authorities or insurance companies. In order to capture the full extent of the flood, open water and especially temporary flooded vegetation (TFV) areas have to be considered. The Sentinel-1 (S-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 63 publications
0
43
0
Order By: Relevance
“…False positives may also occur for flat man-made objects, such as roads, parking lots, and airfields [12]; this was not the case in our case because of the low degree of urbanization in the study area. In contrast, the inclusion of VH data into flood monitoring analyses can be beneficial in comparison to using VV data alone; the effect is, however, study site specific [10], [45]. Moreover, multi-data-source methods can benefit from C-band VH by exploring other properties of this polarization, such as its lower sensitivity to surface water roughness than VV data [12].…”
Section: A Testing Scenarios and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…False positives may also occur for flat man-made objects, such as roads, parking lots, and airfields [12]; this was not the case in our case because of the low degree of urbanization in the study area. In contrast, the inclusion of VH data into flood monitoring analyses can be beneficial in comparison to using VV data alone; the effect is, however, study site specific [10], [45]. Moreover, multi-data-source methods can benefit from C-band VH by exploring other properties of this polarization, such as its lower sensitivity to surface water roughness than VV data [12].…”
Section: A Testing Scenarios and Validationmentioning
confidence: 99%
“…A patchy pattern due to vegetation is often present in nonarid study areas. Several processing steps have been proposed to produce continuous flooding extents, e.g., region growing [7], [12], [17], [46], rule-based algorithms [6], multitemporal analysis [10], [14], [45], wavelet analysis [47], and others.…”
Section: B Flood Mappingmentioning
confidence: 99%
“…Floods in boreal forests were mapped by Voormansik, et al, (2014), who concluded that additional testing of the X-band sensor should be carried out with more detailed information regarding tree species, stand age, height and density. ESA's Sentinel-1 satellite pair offers a valuable SAR data source suitable for monitoring flood conditions (Twele, et al, 2016;Clement, et al, 2018;Ruzza, et al, 2019;Tsyganskaya, et al, 2019;Uddin, et al, 2019), especially in northern latitudes due to nearly daily temporal resolution. However, the land areas are regularly imaged only with VV-and VH-polarizations, which are less useful for detecting floods under forest canopy compared to HH-polarization (see section 2.2)…”
Section: Forest Floodsmentioning
confidence: 99%
“…With all this, on the VV polarization image, the pixels with a backscattering coefficient value not greater than −15 dB are regarded as a body of water, and on the VH polarization image, the pixels with a backscattering coefficient value not greater than −23 dB are regarded as a body of water. These characteristics of water bodies are what past research studies have used [16,[23][24][25][26]. These characteristics also allow us to detect water bodies with periodically frozen ice in winter using the above thresholds.…”
Section: Preliminary Extraction Of Water Bodymentioning
confidence: 82%
“…When the water level is high or the transmission is low, the radar signal is usually attenuated, while when the water level is low relative to the vegetation, double rebound scattering may occur [16]. Some studies have tried to detect water with obvious vegetation canopy on its surface [26,39,40], but most of these studies require the relative heights of vegetation and water surface and the distribution characteristics of vegetation leaves as input parameters of the model. These parameters need to be measured in the wild, so these existing studies are basically limited to small scales.…”
Section: Uncertainty Of This Studymentioning
confidence: 99%